خصوصية المجموعات الافتراضية الجزائرية - داسي، السعدية, غنابزية، مسعودة (جامعة الوادي university of Eloued, 2020)
الملخص: تهدف هذه الدراسة الاثنوغرافية إلى وصف وفهم خصوصية الجماعات الافتراضية على الفسيبوك باعتباره يشكل فضاءا مفتوحا تجتمع فيه مختلف النخب السياسية والتيارات الفكرية والجماعات المحلية والعالمية، فيما باتت الدراسات الحديثة تميل إلى دراسة هذه الجماعات من نواحي عديدة، باعتبارها بديلا وجماعات منافسة للجماعات الواقعية، وفي ظل هذا السياق ارتأينا في هذا البحث إلى دراسة خصوصية الجماعات الافتراضية الجزائرية من خلال مجموعتي "أهل الجزائر" و"الجزائر" المكونتين على أساس جغرافي. ولمعالجة هذا الموضوع اخترنا القيام بدراسة كيفية تعتمد على الملاحظة بالمشاركة على الخط في مرحلة أولى من خلال معايشة ميدان الدراسة، وعلى المقابلة المقننة وغير المقننة في مرحلة ثانية، وهذا بالاستناد إلى المنهج الاثنوغرافي، والاعتماد على عينة قصدية من مستخدمي الفيسبوك في الجزائر والتي تنتمي إلى فئات اجتماعية مهنية ومستويات تعلمية مختلفة، ومن كلا الجنسين، وهذا بغرض فهم السلوك الاجتماعي لهذه الجماعات ومعرفة خصوصيتهم. ومن أهم النتائج التي توصلت إليها الدراسة أن الجماعات الجزائرية الافتراضية هي جماعات شبابية ذكورية بالدرجة الأولى، يستخدمون هويات افتراضية في الغالب للتفاعل والنشاط، مستعملين وسائط مرئية مرفقة بنص أو نصوص مباشرة لعرض مضامين المنشورات التي كانت تطرح من مواضيع دينية وسياسية واجتماعية على الأغلب، فيما يشكلون رأي موحد في بعضها كالمواضيع الاجتماعية والدينية ويختلفون في البعض الاخر كالمواضيع السياسية. Abstract: This ethnographic study aims to describe and understand the privacy of virtual groups on Facebook as it constitutes an open space in which the various political elites, intellectual currents, and local and global groups meet, while modern studies have tended to study these groups in many ways, as an alternative and rival groups to real groups, and in light of this Context We decided in this research to study the privacy of the Algerian virtual groups through the two groups "Ahl Al-Djazair" and " Al-Djazair", which are formed on a geographical basis. To address this issue, we chose to conduct a method study based on observation by participation on the line in the first stage through the experience of the field of study, and on the codified and unregulated interview in a second stage, and this is based on the ethnographic approach, and relying on an intentional sample of Facebook users in Algeria that belong to groups Socio-professional, with different educational levels, and from both sexes, in order to understand the social behavior of these groups and to know their privacy. Among the most important findings of the study is that the hypothetical Algerian groups are primarily male youth groups, who use virtual identities mostly for interaction and activity, using visual media accompanied by text or direct texts to display the contents of the publications that were raised from religious, political and social topics mostly, while they constitute They have a unified opinion on some of them, such as social and religious issues, and they differ in others, such as political ones.
دراسة اثنوغرافية لعينة من صفحات الفيسبوك
مذكرة ماستر إعلام واتصال تخصص سمعي بصري
Keywords: البحث الاثنوغرافي، المجتمعات الافتراضية; Recherche ethnographique, communautés virtuelles; Ethnographic Research, Virtual Communities